One rule does not fit it all: patterns and drivers of stakeholders perspectives of the endangered Iberian wolf - Torres, RT (2022)
Public attitudes are vital for the successful implementation of management strategies and conservation programs. However, contradictory interests among different stakeholders can create important setbacks, creating barriers to achieve conservation goals. The endangered Iberian wolf (Canis lupus signatus) occupies now only 20 % of its historical distribution area, in Portugal, and its reduction was mostly due to direct human persecution. Here, we assessed locals’ attitudes towards the Iberian wolf in northeast Portugal, in a region where humans and wolves coexist for centuries. A total of 323 questionnaires from three different interest groups (general public, livestock owners and hunters) were analysed. We tested the differences in attitude and fear level patterns between the different groups and assessed what socio-demographic factors could be influencing the detected patterns. We found that general attitude towards this carnivore was neutral to positive, probably owing to the low levels of livestock predation and long coexistence with local populations. However, most drivers differed among stakeholders groups. Education, knowledge, and level of fear were strong predictors explaining attitudes towards this endangered species. We stress the importance of assessing attitudes patterns and identifying the socio-psychological factors as necessary tools to facilitate the development of targeted tolerance-promoting strategies. Among other instruments, increasing locals’ tolerance toward the Iberian wolf can be achieved by target education interventions, where the stakeholders can actively take part in discussions to accommodate their needs and expectation, rather than be listeners of the implemented programs.